Flow-Sound Interaction Mechanisms in the Wake of Two Side-By-Side Cylinders. Issue 7 (December 2014) - Arthurs, David; Bolduc, Michael; Ritcey, Adam; Ziada, Samir
The phenomenon of flow-excited acoustic resonance, where periodic flow oscillations are enhanced by a resonant sound field, is a design concern in many engineering applications such as in heat exchangers, piping systems, and cavity flows. This study experimentally examines the phenomenon of flow-excited acoustic resonance for two side-by-side cylinders in a duct with cross-flow. This geometry has been investigated for three cylinder spacing ratios, defined as the center-to-center distance between the cylinders normalized by their diameter, of T/D = 1.25, 1.46 and 2.5, and for a range of acoustic pressure amplitudes. Intermediate and small spacing ratios have been given special attention, as these cases have been found to exhibit bistable flow in the wake in the absence of acoustic resonance. Phase-locked PIV measurements reveal that the self-excited sound field produces a strong oscillatory flow pattern in the cylinder wakes, which is symmetric for large spacing ratios and high acoustic amplitudes, but remains bistable for small spacing ratios, even during very intense acoustic resonances. The aeroacoustic sources and sinks within the flow field, computed using Howe's theory of vortex sound, are compared for the range of spacing ratios and acoustic pressure amplitudes examined in this study.